Graphene Based Sensors for Air Quality Monitoring - Preliminary Development Evaluation - Machado, Denise; Hortigüela, Maria J.; Irurueta, Gonzalo Otero-; Marques, Paula A.A.P.; Silva, Ricardo; Silva, Rui F.; Neto, Victor (Journal of Coating Science and Technology, 2019)
Indoor air pollution can induce adverse health effects on building occupants and pose a significant role in health worldwide. To avoid such effects, it is extremely important to monitor and control common indoor pollutants such as CO2, VOCs, and relative humidity. Therefore, this work focuses on recent advances in the field of graphene-based gas sensors, emphasizing the use of modified graphene that broadly expands the range of nanomaterials sensors. Graphene films were grown on copper by chemical vapor deposition (CVD) and transferred to arbitrary substrates. After synthesis, the samples were functionalized with Al2O3 by ALD and characterized by a large set of experimental techniques such as XPS, Raman, and SEM. The results demonstrated that graphene was successfully synthesized and transferred to SiO2, glass, and polymer. As a proof-of-concept, ALD of Al2O3 was performed on the graphene surface to produce a graphene/metal oxide nanostructure towards the development of nanocomposites for gas sensing. From this perspective, a laboratory prototype device based on measuring the electrical properties of the graphene sample as a function of the gas absorption is under development.